Sistem Fonologi Bahasa Ranau - Darsita, Darsita (Buletin Al-Turas, 2004)
This paper will report about Ranau language, one af the world language that can be classifield as global languageÂ viability. This language represents a unique sound system such as the function of duration and intonation aredistinctive. This article also will describe about Ranau Phonology System. There are two subjects that willÂ be explaned: Firstly tries characterite al and any sounds that can be produced by the human vocal organs in the contextof spoken language, and dly to find vocal and consonant system.Â